Ecological benefits and risks to native salmonids from beaver dam analogs - Meyer, Stacey; McCormick, Joshua L.; Copeland, Timothy; Young, Amber (Frontiers in Ecology and Evolution, 2025)
In degraded river systems, beaver dam analogs (BDAs) are an increasingly popular low-tech treatment used to reduce water velocity, increase floodplain connectivity, activate secondary side channels, and thus increase juvenile salmonid rearing habitat. However, BDAs may benefit non-native species as well, posing a potential conservation risk. In the Lemhi River basin in Idaho, an Intensively Monitored Watershed program quantifies responses of salmonid populations to restoration actions intended to remediate the effects of agricultural development. In 2017, BDAs were installed in Hawley Creek, to improve habitat conditions for native Rainbow Trout (Oncorhynchus mykiss). Non-native Brook Trout (Salvelinus fontinalis) also reside in Hawley Creek. We evaluated native and non-native salmonid responses to BDAs to understand their implications for achieving restoration goals. A BACI analysis was used to evaluate the effects of BDAs on the intrinsic rate of population growth of Rainbow Trout and Brook Trout. Demographic analysis was used to estimate the effects of treatment (i.e., BDA or control) on abundance and demographic rates of Rainbow Trout and Brook Trout. Our results suggested that Brook Trout did not displace Rainbow Trout in sites with BDAs, indicating that BDAs may not greatly change conservation risk to native salmonids. Rainbow Trout abundance and apparent survival in Hawley Creek post-treatment were typically higher than for Brook Trout. Our study suggests that BDAs in degraded western streams did not favor Brook Trout over Rainbow Trout.